2020
DOI: 10.7554/elife.54172
|View full text |Cite
|
Sign up to set email alerts
|

Using the past to estimate sensory uncertainty

Abstract: To form a more reliable percept of the environment, the brain needs to estimate its own sensory uncertainty. Current theories of perceptual inference assume that the brain computes sensory uncertainty instantaneously and independently for each stimulus. We evaluated this assumption in four psychophysical experiments, in which human observers localized auditory signals that were presented synchronously with spatially disparate visual signals. Critically, the visual noise changed dynamically over time continuous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…To form a more reliable percept of the environment, the brain needs to estimate sensory uncertainty (Beierholm et al, 2020). For instance, the magnitude of the CTB is related to the magnitude of uncertainty in sensory measurement and the select cost function (Mamassian & Landy, 2010).…”
Section: The Precision Of the Likelihood And Prior Distributionsmentioning
confidence: 99%
“…To form a more reliable percept of the environment, the brain needs to estimate sensory uncertainty (Beierholm et al, 2020). For instance, the magnitude of the CTB is related to the magnitude of uncertainty in sensory measurement and the select cost function (Mamassian & Landy, 2010).…”
Section: The Precision Of the Likelihood And Prior Distributionsmentioning
confidence: 99%
“…As shown by Bayesian models, the interaction of two multisensory inputs can be decomposed into two contributions: one that depends on the physical discrepancy between the cues, and an overall binding tendency that is independent of the current stimulus (Beierholm et al, 2020; Körding et al, 2007; Odegaard et al, 2015; Park et al, 2021; Wozny et al, 2010). In typical laboratory studies, this overall binding tendency is often considered to be fixed for a given observer, reflecting their belief that the presented multisensory cues are causally related given the context of a specific experimental setting.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the integration bias scales with the relative sensory reliability of the probed modality, in line with the notion of Bayesian optimal reliability weighted cue combination (Ernst and Bulthoff, 2004; Angelaki et al, 2009). A recent study has shown that the brain keeps track of the individual unisensory reliabilities and discounts previous experience in an exponential manner (Beierholm et al, 2020). Hence, our estimates of unisensory reliabilities are shaped by the collective past, which renders the weights assigned to individual sensory inputs during integration history dependent.…”
Section: Resultsmentioning
confidence: 99%